Chromosomal Microarray Analysis in Pediatric Patients with Neurodevelopmental Disorders and Congenital Anomalies: A Two-Center Experience - Hatice Koçak Eker; Sezin Canbek (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
Chromosomal microarray analysis (CMA) is a first-tier diagnostic tool for children with neurodevelopmental disorders and congenital anomalies; however, interpretation of variants of uncertain significance (VUS) remains challenging. This study aimed to characterize the copy number variant (CNV) spectrum in pediatric patients with congenital anomalies and/or dysmorphic features, focusing on VUS interpretation through segregation analysis and detailed phenotype–genotype correlation. We retrospectively evaluated 28 pediatric patients with abnormal CMA results referred to two tertiary genetics clinics between 2021 and 2022. Indications included neurodevelopmental delay, intellectual disability, dysmorphism, and/or congenital anomalies. CNVs were classified according to 2020 ACMG/ClinGen standards. Parental segregation analysis was performed for 15 CNVs in 13 families, with particular attention to gene disruption caused by CNV breakpoints. The cohort included 16 males and 12 females, with a mean age of 5.28±4.39 years. Thirty-four CNVs were identified, including 14 deletions and 20 duplications; seven were pathogenic/likely pathogenic and 27 were VUS. Segregation analysis identified five de novo, six maternal, and four paternal variants. A 2q22.2 gain disrupting KYNU at intron 12 was identified in a patient with VACTERL-like features. Three patients had additional karyotypic abnormalities, highlighting the complementary role of CMA. A de novo 4p16.3 duplication disrupting both HTT and ADD1 was also identified. Our findings highlight the importance of detailed phenotyping, breakpoint analysis, and segregation studies in interpreting CNVs, particularly VUS and rare intragenic disruptions. Integrating genomic findings with clinical features and inheritance patterns may improve phenotype–genotype correlation and support the identification of candidate loci.